Periodic orbits and gravitational wave radiation in short hair black hole spacetimes for an extreme mass ratio system - Lai Zhao; Meirong Tang; Zhaoyi Xu (European Physical Journal C: Particles and Fields)
Abstract For a short hair black hole(BH) that bypasses the “no-short-hair” theorem, its hair parameters have a significant impact near the event horizon and may thus carry the internal information of the BH. This paper studies the influence of the hair parameter $$Q_m$$ Q m and the structural parameter $$k$$ k of the short hair BH on the periodic orbits of particles and gravitational wave radiation in the extreme mass ratio(EMR) system. The research results show that $$Q_m$$ Q m has a significant impact on the radius of the orbit, angular momentum, and the $$E-L$$ E - L space. A larger value of $$k$$ k weakens this effect and makes it degenerate with the Schwarzschild BH. In addition, an increase in $$Q_m$$ Q m or a decrease in $$k$$ k will lead to a reduction in the period of gravitational waves and a significant enhancement of the signal amplitude. These results provide new observational means for distinguishing short hair BH from classical BH and also offer new insights for verifying the no-hair theorem and understanding the physical behaviors near the event horizon.